Oxygen isotope fractionation between hydroxyapatite (HAP)-bound carbonate and water at low temperatures - Ie, Kesia (My University, 2016)
Calcium phosphates are important compounds as they exist in natural aqueous systems such as rivers, lakes, ocean, and soil. These calcium phosphates are widely used to provide information on paleotemperatures as well as many anthropological features, such as paleodiets. One of the most ubiquitous forms of calcium phosphate is hydroxyapatite (Ca10(PO4)6(OH)2) which is a major component of hard tissue such as bones, fossils, and tooth enamel. The oxygen isotope systematics in the hydroxyapatite associated with carbonate-water system will provide further information to allow for the reconstruction of terrestrial and marine environments. For example, Fricke et al. (1998) used oxygen isotope analysis of the carbonate components of hydroxyapatite in tooth enamel of mammals to investigate changes in terrestrial climate. Therefore, the purpose of this research study was to examine the oxygen isotope systematics in inorganic carbonate-bearing hydroxyapatite and water at low temperatures. This Master’s thesis followed and modified the methods described in Lécuyer et al. (2010) in an attempt to synthesize hydroxyapatite crystals and carbonate-bearing hydroxyapatite. The crystals synthesized were characterized in terms of several conditions (i.e., influence of mixing rate and maturations, pH, and concentrations of NaHCO3). Methods to produce hydroxyapatite were developed and analyzed using X-Ray diffraction analysis. The results demonstrated a strong dependence of pH in the hydroxyapatite solutions. Moreover, the effect of concentrations of NaHCO3 was deemed to be essential in order to obtain the desired amount of structural carbonates in the hydroxyapatite crystals. Furthermore, this research evaluated the temperature dependence of oxygen isotopic fractionation between HAP-bound carbonate and water at 10, 25, and 40 oC. Our study is the first to assess the two mixing-rates experiments with different maturations (7 and 14 days) on the oxygen isotope effects and fractionation behaviour between HAP-bound carbonate and water. Both maturation time and the effect of initial concentration of NaHCO3 were found to be the most important in determining the equilibrium conditions in our experiments.
Keywords: Hydroxyapatite; Synthetic apatite; Oxygen; Stable isotope geochemistry